Secondary syphilis with liver involvement in a liver transplant recipient. Issue 1 (16th August 2020) - Ferrándiz‐Pulido, Carla; Ferrer, Berta; Salcedo, Maria Teresa; Velasco, Marta; Len, Oscar; Castells, Lluis
Abstract: Syphilis is capable of compromising almost any organ; however, syphilitic hepatitis is a rare manifestation that has been described most often in HIV‐infected patients. Herein, we present a 33‐year‐old male liver transplant recipient who presented with progressive liver dysfunction characterized by mild ALT elevation and rising cholestasis, malaise, skin rash, and alopecia. Skin biopsy was characteristic of secondary syphilis, confirmed by both skin and liver biopsy‐positive immunohistochemical staining for Treponema pallidum . The patient was treated with benzathine penicillin G 2.4 million units IM q week × 3 weeks. Three months later, the patient was asymptomatic and recovered from his general malaise. He showed no skin lesions and demonstrated complete regrowth of the hair on his scalp, beard, and eyebrows. The presence of liver dysfunction with cholestasis in a transplant recipient should alert transplant providers to the possibility of syphilitic hepatitis, particularly in men who have sex with men. Though not an early manifestation, cutaneous signs of secondary syphilis may be a helpful diagnostic indicator in most cases.